Representing Hip Hop Histories, Politics and Practices in Australia - Dowsett, Sudiipta; Marie, Lucas; Rodger, Dianne; Leigh Saunders, Grant (Taylor & Francis, 2024)
This long-awaited volume is the first edited collection to focus entirely on Hip Hop in Australia. Bringing together both scholarly and practitioner perspectives, across 11 chapters, contributors explore the diversity of identities, communities, practices, and expressions that make-up Hip Hop in Australia, including Emceeing/ music production, Graffiti and Breaking. The theoretical and methodological frameworks used include ethnographic and autoethnographic research and writing, discourse analysis, Indigenous methodologies, textual analysis and archival research. Some authors present their contributions in academic chapters, while others use creative formats. The book showcases how Hip Hop is understood and lived across numerous settings in Australia, making important contributions to global Hip Hop studies and scholarship in related fields such as popular music, youth culture and First Nations Studies. It will prove essential reading for students, academics, and practitioners interested in Hip Hop, social justice, popular culture, music and dance in Australia.